The Effect of Antihypertensive Drugs (Diuretic, Non-Diuretic Types) on Serum Electrolyte Levels (Na+, K+, Cl-) in Hypertensive Patients - Irmawati, Irmawati; Nidianti, Ersalina; Anggraini, Rahayu; Kartika Sari, Nathalya Dwi (Jurnal Laboratorium Khatulistiwa, 2025)
Hypertension is one of the most common cardiovascular diseases and is still a major problem in the world. The prevalence of hypertension continues to increase every year, especially increasing most rapidly in developing countries (80% in the world). Treatment of hypertension is adjusted to the results of the examination, the cause and the patient's health condition. Antihypertensive drugs are divided into diuretic and non-diuretic types. This study aims to evaluate the effect of antihypertensive drugs on serum electrolyte levels in hypertensive patients. This type of study is observational analytic with a cross-sectional approach, on the effect of diuretic and non-diuretic antihypertensive drugs on hypertensive patients with a sample population of 30 samples. The method of examining the levels of electrolytes Na +, K +, Cl- is Ion selective electrolyte (ISE) with the provisions of normal sodium values of 135-145 mmol / L, potassium 3.5-5.5 mmol / L, chloride 94-110 mmol / L. The results of statistical tests showed that the average value of those consuming diuretic antihypertensive drugs was 141.06 mmol/L sodium, 4.27 mmol/L potassium, 106.55 mmol/L chloride and those consuming non-diuretic antihypertensive drugs were 137.89 mmol/L potassium, 4.08 mmol/L chloride 102.29 mmol/L. From the results of the Kruskal Wallis test, the p-value for sodium levels was 0.164, potassium 0.221, chloride 0.046, which means that there is no effect on hypertensive patients consuming diuretic and non-diuretic antihypertensive drugs on serum electrolyte levels of sodium, potassium, but there is a significant effect on chloride levels.